Comportamento do consumidor: um estudo sobre os consumidores de livros pela internet - Piva, Wagner de Oliveira (2010)
Based on the shopping decision theory is investigated in the the course of this dissertation, the motive that brings consumers buying technical books in the Internet, there are factors like motivation to acquire technical books, how the consumer shops, how he decides over some store, which ways he prefers to pay and what he thinks about the experience of buying books online. This dissertation justifies by itself, because brazilian's e-commerce grows every year and understand what brings the consumers acquire that new way of retail is important to academics and professionals. The choice by this book industry took place because, according with several reports available, books is the solidest online product in numbers, about 20 per cent of everything that is sold over the internet refers to books or magazines. The work was divided in two research stages. The first step was a literature review about the work and in the second step was made a research with online technical books consumers. The research envolved the analysis of 837 online technical books consumers questionnaires, clients of a specialized bookstore in this area. The results show that online technical books consumers are satisfied with the online bookstore service and the determinate factors to acquire technical books by Internet are convenience and price. Its noticed too that credict cards are the most common way of payment